2021
DOI: 10.1186/s13059-020-02258-y
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing landscapes in Arabidopsis thaliana across tissues and stress conditions highlight major functional differences with animals

Abstract: Background Alternative splicing (AS) is a widespread regulatory mechanism in multicellular organisms. Numerous transcriptomic and single-gene studies in plants have investigated AS in response to specific conditions, especially environmental stress, unveiling substantial amounts of intron retention that modulate gene expression. However, a comprehensive study contrasting stress-response and tissue-specific AS patterns and directly comparing them with those of animal models is still missing. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 83 publications
8
133
0
Order By: Relevance
“…These differences in the regulation of AS and GE reflect divergent evolutionary processes of gene expression and AS level regulation in plants. A recent study investigating the regulation of AS and GE in Arabidopsis under stress conditions (Martín et al, 2021 ) found the core genes regulated by AS and GE in response to internal and external stimuli shared few common members. One clear difference is that RNA binding proteins (RBPs) were significantly enriched in the AS core sets, whereas GE core gene sets were depleted in RBPs but significantly enriched in DNA‐binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in the regulation of AS and GE reflect divergent evolutionary processes of gene expression and AS level regulation in plants. A recent study investigating the regulation of AS and GE in Arabidopsis under stress conditions (Martín et al, 2021 ) found the core genes regulated by AS and GE in response to internal and external stimuli shared few common members. One clear difference is that RNA binding proteins (RBPs) were significantly enriched in the AS core sets, whereas GE core gene sets were depleted in RBPs but significantly enriched in DNA‐binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study, a batch of RNA binding proteins and RNA recognition motif‐containing family proteins enriched in identified AS event sets, including tissue‐, stage‐, species‐specific, biased and polyploidization‐altered AS events, indicating this regulatory specialization is widespread. Moreover, this AS landscapes study in Arabidopsis discovered that the different AS event types were differentially regulated under stress or in different tissues with RI showing the most diverse changes (Martín et al, 2021 ). This is similar to our conclusion on the comparison of AS event types among developmental stages, tissues and subgenomes (Figure 1 ), revealing the complexity of AS spatiotemporal regulation as a key element in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Neural regulation (difference in average PSI of neural and non-neural samples) for each Nova -regulated exon was calculated using data from VastDB for mm10 and dm6 [ 29 ], and through the script Get_Tissue_Specific_AS.pl [ 66 ]. Analysis of splicing-related features was performed with matt cmpr_exons [ 51 ] v1.3.0 and a selection of features was plotted in Additional file 1 : Figure S3.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, the defined TSS and TES clearly demonstrated variation in TSS and TES for many genes and re-analysis of the cold time-series data with AtRTD3 identified differential TSS and TES usage due to low temperature and light/dark conditions. It will now be possible to examine transcriptional and post-transcriptional regulation of gene expression involving differential TSS and TES usage demonstrated here and the impact of AS in UTRs [53,67] during development and in response to abiotic and biotic stresses. Differential TSS and TES usage illustrates novel regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%